Transcranial Focused Ultrasound to the Right Prefrontal Cortex Improves Mood and Alters Functional Connectivity in Humans - Sanguinetti, Joseph L.; Hameroff, Stuart; Smith, Ezra E.; Sato, Tomokazu; Daft, Chris M. W.; Tyler, William J.; Allen, John J. B. (Frontiers in Human Neuroscience, 2020)
Transcranial focused ultrasound (tFUS) is an emerging method for noninvasive neuromodulation akin to transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS). tFUS offers several advantages over electromagnetic methods including high spatial resolution and the ability to reach deep brain targets. Here we describe two experiments assessing whether tFUS could modulate mood in healthy human volunteers by targeting the right inferior frontal gyrus (rIFG), an area implicated in mood and emotional regulation. In a randomized, placebo-controlled, double-blind study, participants received 30 seconds of 500 kilohertz (kHz) tFUS or a placebo control. Visual Analog Mood Scales (VAMS) assessed mood four times within an hour (baseline and three times after tFUS). Participants who received tFUS reported an overall increase in Global Affect (GA), an aggregate score from the VAMS scale, indicating a positive shift in mood. Experiment 2 examined resting-state functional (FC) connectivity using functional magnetic resonance imaging (fMRI) following 2 minutes of 500 kHz tFUS at the right inferior frontal gyrus (rIFG). As in Experiment 1, tFUS enhanced self-reported mood states and also decreased FC in resting-state networks related to emotion and mood regulation. These results suggest that tFUS can be used to modulate mood and emotional regulation networks in the prefrontal cortex.